EFEKTIVITAS PEMBELAJARAN FISIKA BERBASIS MULTIREPRESENTASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA MATERI MOMENTUM DAN IMPULS KELAS X SMA - Dandi Rahmana; Zuhdi Ma’aruf; Muhammad Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The ability to understand concepts of physics is an absolute requirement for the success of a physics lesson. The low understanding of physics concepts is a problem that must be resolved. One way that is considered to be able to overcome problems in the teaching and learning process is by applying multi-representation-based physics learning. This study aims to determine the effectiveness of multi-representation-based physics learning in increasing students' conceptual understanding of momentum and impulse material. The type of research used is quasi-experimental research with the Nonequivalent Post-test Control Group Design. This research was conducted at SMA Negeri Pintar Riau Province by using a concept understanding test on Momentum and Impulse material. The research sample was class X IPA 1 with a total of 25 people as the experimental class and class X IPA 2 with a total of 25 people as the control class. The instrument used in data collection was a test on the results of understanding the concept of momentum and impulse material for class X which consisted of 21 reasoned multiple choice questions. The data analysis used was descriptive analysis through the level of understanding of the concept and the effectiveness of learning and inferential analysis through the normality test, homogeneity test, and the Independent T-Test with the help of SPSS 20. The results showed that the understanding of the concepts of the experimental students and the control class was different, from the average score of the experimental class is higher than the control class. From this study, it can be concluded that multi-representation-based physics learning can improve students' understanding of the concept of momentum and impulse material in class X High School.Keywords: Learning Effectiviness, Multiple- representations, Concept Mastery